2021
DOI: 10.1111/ijcs.12744
|View full text |Cite
|
Sign up to set email alerts
|

‘Crying over spilt milk?’ Effect of post‐consumption dissonance on coping behaviour for online purchases

Abstract: The global e-commerce market is expected to be around USD 66,932 billion by 2030, 1 with India emerging as the second-largest digital economy with a projected 1 billion users and an e-commerce market size of USD 300 billion. 2 The COVID-19 induced restrictions have caused a strong rise in the industry, especially in India, with Google investing USD 4.5 billion in JioMart. 3 However, the enhanced demand for e-commerce during the COVID-19 period, coupled with product shortages, induced the consumer perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 136 publications
(205 reference statements)
1
21
0
Order By: Relevance
“…Negative information conveyed to a person has a stronger influence on the person when they are in a negative emotional state ( Jin and Oh, 2021 ). According to emotion repair theory, negative emotions encourage consumers to adopt response strategies, such as seeking social support to mitigate their anger, to seek an improvement in their environment ( Mahapatra and Mishra, 2021 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Negative information conveyed to a person has a stronger influence on the person when they are in a negative emotional state ( Jin and Oh, 2021 ). According to emotion repair theory, negative emotions encourage consumers to adopt response strategies, such as seeking social support to mitigate their anger, to seek an improvement in their environment ( Mahapatra and Mishra, 2021 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…The concept of cognitive dissonance has often been used to discuss the post‐purchase stage (Lee, 2015; Mahapatra & Mishra, 2021; Sharifi & Esfidani, 2014). For example, Mahapatra and Mishra (2021) found that cognitive and affective components of post‐consumption dissonance have a positive influence on negative emotions.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…The concept of cognitive dissonance has often been used to discuss the post‐purchase stage (Lee, 2015; Mahapatra & Mishra, 2021; Sharifi & Esfidani, 2014). For example, Mahapatra and Mishra (2021) found that cognitive and affective components of post‐consumption dissonance have a positive influence on negative emotions. O'Neill and Palmer (2004) show that individuals are likely to use cues to reduce cognitive dissonance, thereby narrowing the gap between their prior expectations and post‐purchase perceptions.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations